2023
DOI: 10.1002/jsfa.12801
|View full text |Cite
|
Sign up to set email alerts
|

A two‐year study on the occurrence and concentration of mycotoxins in corn varieties with different endosperm textures

Abstract: BACKGROUNDMycotoxin monitoring in cereal grains has great importance in the food and feed industries. This study evaluated mycotoxin contamination in corns with different endosperm textures in 2 years of cultivation. Samples of dent, semi‐dent, flint and semi‐flint corns from field experiments were analyzed by high‐performance liquid chromatography coupled with tandem mass spectrometry (HPLC‐MS/MS).RESULTSOccurrences of fumonisins B1 (FB1) and B2 (FB2) in 2020 were 45.72% (mean 270 μg kg−1) and 35.89% (94.97 μ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…The analysis of meteorological data collected in the experimental field over the three years of the present study enabled the identification of variability among the years and the discussion of the potential impact of these conditions on crop yield and grain quality. It has already been demonstrated that the meteorological variables from different years exert some influence on the nutritional and mycotoxicological composition of different corn hybrids [23,24]. Data from 2020, 2021, and 2022 reveal challenging climatic conditions for corn cultivation in the region where the present study was conducted.…”
Section: Discussionmentioning
confidence: 86%
“…The analysis of meteorological data collected in the experimental field over the three years of the present study enabled the identification of variability among the years and the discussion of the potential impact of these conditions on crop yield and grain quality. It has already been demonstrated that the meteorological variables from different years exert some influence on the nutritional and mycotoxicological composition of different corn hybrids [23,24]. Data from 2020, 2021, and 2022 reveal challenging climatic conditions for corn cultivation in the region where the present study was conducted.…”
Section: Discussionmentioning
confidence: 86%